Recent Progress in Improving Rate Performance of Cellulose-Derived Carbon Materials for Sodium-Ion Batteries - Wang, Fujuan; Zhang, Tianyun; Zhang, Tian; He, Tianqi; Ran, Fen (Nano-Micro Letters, 2024)
Cellulose-derived carbon is regarded as one of the most promising candidates for high-performance anode materials in sodium-ion batteries; however, its poor rate performance at higher current density remains a challenge to achieve high power density sodium-ion batteries. The present review comprehensively elucidates the structural characteristics of cellulose-based materials and cellulose-derived carbon materials, explores the limitations in enhancing rate performance arising from ion diffusion and electronic transfer at the level of cellulose-derived carbon materials, and proposes corresponding strategies to improve rate performance targeted at various precursors of cellulose-based materials. This review also presents an update on recent progress in cellulose-based materials and cellulose-derived carbon materials, with particular focuses on their molecular, crystalline, and aggregation structures. Furthermore, the relationship between storage sodium and rate performance the carbon materials is elucidated through theoretical calculations and characterization analyses. Finally, future perspectives regarding challenges and opportunities in the research field of cellulose-derived carbon anodes are briefly highlighted. Highlights: 1 Enhancing rate performance of cellulose-derived hard carbon anodes from the view of cellulose molecular, crystalline, and aggregation structure is explored. 2 Relationship of storage sodium and rate performance according to theoretical calculation and characterization analysis is illustrated. 3 Cellulose intrinsic microstructure, conversion relationship between the allotropes of cellulose, and the critical influences on cellulose-derived carbon structure are discussed.